2017
DOI: 10.4236/ojgas.2017.71003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ultrasonically Guided Fine Needle Cytology in the Diagnosis of Focal Liver Lesions in Sulaimani-Kurdistan Region, Iraq

Abstract: Background: Fine Needle Aspiration Cytology (FNAC) under image guidance has gained increasing acceptance as the diagnostic procedure of choice for patients with focal hepatic lesions. It can be performed percutaneously or endoscopically. FNA may also be performed at laparoscopy or laparotomy under direct vision when image guided FNA fails to provide diagnostic tissue. In experienced hands, FNA is safe, minimally invasive, accurate, and cost-effective. However, the main aim of this study is to assess the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
4
0
0
Order By: Relevance
“…In present study out of 43 cases of metastatic carcinoma, 38 cases showed normal serum AFP levels while 5 cases of metastatic carcinomas showed raised serum AFP levels. These results were in line with study done by Alkarboly et al [13] The present study showed that out of 5 cases of metastatic carcinomas having raised AFP levels, maximum value of serum AFP (345.61ng/mL) was seen with MDA followed by MDPDC (13.45±38.91 ng/mL) ( Table 2). All the cases diagnosed as MDSCC, inadequate and inconclusive cases had serum AFP levels of less than 8.5ng/mL.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In present study out of 43 cases of metastatic carcinoma, 38 cases showed normal serum AFP levels while 5 cases of metastatic carcinomas showed raised serum AFP levels. These results were in line with study done by Alkarboly et al [13] The present study showed that out of 5 cases of metastatic carcinomas having raised AFP levels, maximum value of serum AFP (345.61ng/mL) was seen with MDA followed by MDPDC (13.45±38.91 ng/mL) ( Table 2). All the cases diagnosed as MDSCC, inadequate and inconclusive cases had serum AFP levels of less than 8.5ng/mL.…”
Section: Resultssupporting
confidence: 93%
“…In the present study showed that out of 56 cases, 28.6% of the cases had jaundice. These results were concordant with the study done by Alkarboly et al [13] While in study conducted by Ahuja et al only 12% cases presented with jaundice. [12] In study done by Sood et al 22.9% cases had history of alcohol abuse and considered it as an important etiological factor for various hepatic lesions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations